Intelligent automotive vehicle safety system / Nazuha Fadzal - Fadzal, Nazuha (2005)
This paper presents a project on the intelligent automotive vehicle safety system that provides automatic control action to the vehicle braking system. At the same time, the system functions for effective assessment of driver vigilance and warning according to traffic risk estimation. An obstacle detection system for an automotive vehicle detects obstacles ahead of the vehicle and finds the dynamic relativity between the vehicle and each of the obstacles [7]. Based on the dynamic relativity, information relating to a danger level between the vehicle and each obstacle is operated on so as to make a danger judgment [7].